(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Return behavior in GDR markets reveals that out of 1070serial correlation coefficients, 427 (39.91 per cent) were positive and 549(51.31 per cent) were negative values. While the remaining, 94 (8.78 per cent)had experienced zero coefficients signifying the absence of interdependence ofany trend for GDR stock returns. As inferred in the earlier sections, dominanceof negative serial correlation coefficient values points to the depressed stockprices in this context too. In addition, 183 (17.10 per cent) serialcorrelation coefficients were considered significant at 5 per cent level ofsignificance. Such a higher incidence of significant correlation coefficientspoints towards the traces of interdependence of stock return. At higher levelof significance (1 per cent) this interdependence has appeared to reducesubstantially (9.44 per cent). It implies that the lower incidence of themagnitude of correlation coefficients under reference. When the magnitude ofserial correlation coefficients examined in relation to their probable error,it reveals that 681 coefficients were less than the respective probable errors.It points to the lower magnitude of serial correlation coefficients. On thewhole, results presented above, points towards the market efficiency of stocksin the GDR markets in a broader perspective. It was also noted the significanceof 66 coefficients were significant at 5 per cent level with one week lags. Itimplies the serial dependence in stock returns. The traces of such dependencewere also discerned up to the lag of 7-week period. This is a profounddemonstration of week form of stock market efficiency with very little fad andbubbles. Therefore, it may be inferred that the GDR markets are relatively moreefficient as compared to their domestic counterparts.